The Role Of The New Zealand Government In Handling Terrorism Through The Media - Andi Moh. Ghalib; Anang Puji Utama; M Adnan Madjid; Pujo Widodo (CV. AFDIFAL MAJU BERKAH, 2023)
New Zealand, which is known as a peaceful country, is faced with the problem of terrorism. Terrorism cases that occur based on the existence of Islamophobic culture and immigrants entering New Zealand also have a connection with the role of mass media in a cause that concerns politics and government. The purpose of this study is to describe the dynamics of terrorism that occurs in New Zealand, as well as the role of the government in solving terrorism through mass media. The method used is a qualitative method with a type of descriptive approach through literature study. Based on the results of the study, it can be understood that the dynamics of terrorism that occur are so complex that then the resolution of terrorism cases is carried out by the government by making policies against actors involved in terrorism tragedies, especially immigrant perpetrators, and collaborating with human rights organizations established by the Foundation Against Islamophobia and Racism (FAIR) which aims to advocate for the human rights of independent Muslims based in New Zealand in counteract Islamophobia. In addition, this article helps to understand that the Government through the Prime Minister of New Zealand also met several Muslim community leaders in Christchurch where he ensured that the New Zealand Government will guarantee the security of every citizen and guarantee the freedom to worship and guarantee the freedom to express the culture and religion of each citizen and with the help of the media in the aftermath of the tragedy of terrorism is expected to reduce the circulation of videos of terror attacks so as not to provoke the community by traumatic, but help victims out of fear of conflict that occurs. The role of the government in efforts to maintain the integrity of the country's territory through cross-sectoral communication and cooperation can then be utilized by local actors to solve problems and participate in maintaining national security.